2021
DOI: 10.1007/s11547-020-01331-7
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of acute ischemic stroke due to tandem lesions of the anterior cerebral circulation: a multicentric Italian observational study

Abstract: Purpose Acute ischemic stroke (AIS) due to tandem lesions (TLs) of extracranial Internal Carotid Artery and Anterior Cerebral Circulation are challenging for endovascular treatment (EVT). This study aims to evaluate feasibility, safety and efficacy of EVT for TLs’ AIS, with or without emergent carotid artery stenting (eCAS), in a real-life scenario. Methods Retrospective review of prospectively collected non-randomized thrombectomy databases from five stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…Our search detected 1601 citations. Overall, 63 studies were potentially eligible for inclusion, and 46 reached qualitative synthesis11–18 23–60 (figure 1 for PRISMA flow-chart). Among them, 17 observational studies directly compared eCAS and no-stenting, while the remainder focused on a single approach (online supplemental table S1 for included study baseline features).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our search detected 1601 citations. Overall, 63 studies were potentially eligible for inclusion, and 46 reached qualitative synthesis11–18 23–60 (figure 1 for PRISMA flow-chart). Among them, 17 observational studies directly compared eCAS and no-stenting, while the remainder focused on a single approach (online supplemental table S1 for included study baseline features).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the included studies were of moderate to high quality (online supplemental table 1) . The risk of bias was high in some studies, mainly due to ascertainment bias and comparability: 11 studies did not report the intraprocedural or postprocedural medication14 17 25 34 35 44 46 47 49 51 52 (online supplemental figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior IVT (in eligible patients) appears to be safe and to further improve recanalization rates [206,209,210]. Bracco et al [211] have recently reported "hemodynamic" tandem occlusion with an acute total or sub-total occlusion of the extracranial ICA without sufficient collateral compensation. Emergent stenting restoring the antegrade blood flow might be crucial [211].…”
Section: Special Situations 271 Tandem Occlusionsmentioning
confidence: 99%